2022
DOI: 10.1177/15330338221090353
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Treatment Models of Advanced Gastric Cancer

Abstract: The prognosis of advanced gastric cancer (AGC) is extremely poor, and the therapeutic effect of traditional palliative chemotherapy is far from satisfactory. To overcome this bottleneck, palliative surgery resection, perioperative chemotherapy combined with surgical resection, hyperthermic intraperitoneal chemotherapy (HIPEC), pressurized intraperitoneal aerosol chemotherapy (PIPAC), radiation therapy, molecular-targeted therapy have been explored in AGC. Although considerable progress has been achieved, there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 87 publications
0
3
0
Order By: Relevance
“…Studies have reported a 5-year survival rate of > 90% for early-stage GC; however, early diagnosis remains limited, with most patients diagnosed at an advanced stage 16 . Recently, the combination of chemotherapeutic and targeted therapies as first-line therapy for advanced GC has improved clinical efficacy, but the prognosis has not substantially improved 17 . Hence, there is an urgent need to identify specific biomarkers to determine the prognosis of patients with GC.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported a 5-year survival rate of > 90% for early-stage GC; however, early diagnosis remains limited, with most patients diagnosed at an advanced stage 16 . Recently, the combination of chemotherapeutic and targeted therapies as first-line therapy for advanced GC has improved clinical efficacy, but the prognosis has not substantially improved 17 . Hence, there is an urgent need to identify specific biomarkers to determine the prognosis of patients with GC.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that the drug sensitivity test on PD‐CRC organoids can predict patient outcomes with 100% sensitivity, 42 , 43 even if some intra‐tumor heterogeneity is lost in the spheroid/organoid line. 44 Our PD–GC‐SC spheroids can be utilized to investigate new molecular targeted therapies and their companion diagnostics for patient selection, 45 , 46 as we recently identified a subset of PD–CRC‐SC spheroid lines that responded to fibroblast growth factor receptor inhibitors. 47 , 48 Additionally, the genomic and expression profiles of GC‐SC spheroids will help determine novel molecular subtypes and diagnostic gene signatures.…”
Section: Discussionmentioning
confidence: 99%
“…Although these agents improve treatment outcomes and the overall survival rates of patients with gastric cancer, most patients with advanced-stage cancer are excluded from molecularly targeted treatment and have a poor prognosis, with a 5-year relative survival rate of 6% [ 4 ]. As a result, the development of new targeted drugs to prolong the survival of patients with advanced gastric cancer is a top priority [ 5 ].…”
Section: Introductionmentioning
confidence: 99%